Experimental validation of pressure swing regeneration for faster cycling in sorption enhanced dimethyl ether synthesis. Issue 88 (13th October 2020) - van Kampen, Jasper; Booneveld, Saskia; Boon, Jurriaan; Vente, Jaap; van Sint Annaland, Martin
Abstract : For the first time, high single-pass production of dimethyl ether from CO2 -rich feedstock is demonstrated using pressure swing regeneration alone, allowing enormous increase in productivity. Abstract : Sorption enhanced dimethyl ether synthesis (SEDMES) is a novel DME production route from CO2 -rich feedstocks. In situ water removal by adsorption results in high single-pass conversions, thereby circumventing the disadvantages of conventional routes, such as low carbon efficiency, energy intensive downstream separation and large recycling. The first-time demonstration of pressure swing regeneration with 80% single-pass carbon selectivity to DME allows for an enormous increase in productivity. Already a factor four increase compared to temperature swing regeneration is achieved, unlocking the potential of SEDMES as a carbon utilisation technology.